Thermodynamics of deposition flux-dependent intrinsic film stress - Amirmehdi Saedi (Nature Portfolio, 2016)
Vapour deposition on polycrystalline films can lead to unexpectedly high and reversible compressive stress, the origin of which remains unclear. Here, the authors show, using thermodynamic arguments, that entropic effects in the extremely dilute adatom gas on the surface play a major role.